2021
DOI: 10.2147/cmar.s332571
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Drug-Eluting Bead-Transcatheter Arterial Chemoembolization After Lipiodol-Based Transcatheter Arterial Chemoembolization Failure for Patients with Advanced Hepatocellular Carcinoma

Abstract: Purpose: To investigate the potential safety and efficacy of drug-eluting bead-transcatheter arterial chemoembolization (DEB-TACE) in treating TACE-refractory hepatocellular carcinoma (HCC). Methods: We retrospectively evaluated the treatment outcomes of DEB-TACE for 41 HCC nodules in 30 patients who were refractory to conventional TACE (c-TACE) according to tumor response. The antitumor response was evaluated according to mRECIST criteria, and changes in alpha-fetoprotein (AFP), albumin-bilirubin score, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The beads employed in DEB-TACE are mainly biocompatible polymers-based hydrogels including polyvinyl alcohol (PVA)-based hydrogels which are sulphonated for binding of anticancer drugs [ 9 ]. The anticancer agents are delivered to the target site upon occlusion of the beads in the vasculature, which embolizes them, and subsequently, the drug is released in the target site [ 10 ]. It is currently unclear whether DEB-TACE or c-TACE should be used for a specific patient in the absence of randomized-controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…The beads employed in DEB-TACE are mainly biocompatible polymers-based hydrogels including polyvinyl alcohol (PVA)-based hydrogels which are sulphonated for binding of anticancer drugs [ 9 ]. The anticancer agents are delivered to the target site upon occlusion of the beads in the vasculature, which embolizes them, and subsequently, the drug is released in the target site [ 10 ]. It is currently unclear whether DEB-TACE or c-TACE should be used for a specific patient in the absence of randomized-controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the ALBI classification has higher prognostic value than the Child-Pugh classification. 21–23 The presence of portal vein thrombosis increases the risk of metastasis and portal hypertension, leading to a higher likelihood of gastrointestinal bleeding, ascites, and liver failure. It is a significant factor affecting the prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It blocks the blood supply of the tumor and accumulates high concentrations of chemotherapeutic drugs in the tumor to kill tumor cells to the greatest extent. 18 , 19 However, TACE can lead to ischemia and hypoxia of embolic tissue cells, stimulate the expression of VEGF in the residual lesions, thus promoting tumor angiogenesis and causing tumor recurrence and metastasis. At the same time, the long-term chronic inflammatory response of the tumor-bearing liver can upregulate PD-1 receptors and promote the spontaneous apoptosis of immune cells.…”
Section: Discussionmentioning
confidence: 99%